Fluktuasi dan Kelimpahan Fitoplankton di Danau Laguna Ternate Maluku Utara - Yuliana Yuliana; Thamrin Thamrin (Jurnal Perikanan Universitas Gadjah Mada, 2007)
The objective of this research was to know the fluctuation and abundance of phytoplankton at Laguna Lake, North Moluccas. This research was conducted for 3 periods, from June to July 2005. Sampling of plankton were taken biweekly in 4 stations and 3 depths (0, 5, and 10 m) by filtration method.The results showed that there were 9 genera from 3 classes: Bacillariophyceae (6 genera), Cyanophyceae (2 genera), and Dinophyceae (1 genera). Plankton abundance on period I ranged 1.14 x 104-3.49 x 104 ind/l, period II ranged 7.64 x 103 -4.73 x 104 ind/l, and period III ranged 9.29 x 103-3.78 x 104 ind/l, the highest on period II (3.19 x 105 ind/l) and the lowest on period I (2.49 x 105 ind/l). The phytoplankton abundance in each station were station 1 = 9.29 x 103-4.73 x 104 ind/l, station 2 = 1.51 x 104-4.52 x 104 ind/l, station 3 = 7.64 x 103-3.45 x 104 ind/l, and station 4 = 1.14 x 104-3.49 x 104 ind/l. The highest phytoplankton abundance was in station 2 (2.45 x 105 ind/l) and the lowest in station 4 (1.68 x 105 ind/l). Whereas, phytoplankton abundance based on depth were 0 m = 9,29 x 103-3,92 x 104 ind/l, 5 m = 7,64 x 103-4,73 x 104 ind/l, and 10 m = 1,18x 105-3,7 x 105 ind/l, the highest on 10 m (2.91 x 105 ind/l) and the lowest on 0 m (2.49 x105 ind/l). The range value of biological index such as diversity index (H’) on period I was 0,5276-1,1853, period II was 0,6138-1,1635, and persiod III was 0.6276-1.2264; equitability index (E) on period I was 0.4422-0.8550, period II was 0.4725-0.8393, and period III was 0.5674-0.8575; and dominant index (D) on period I was 0.3403-0.7032, period II was 0.3584-0.6597, and period III was 0.3195-0.6647.